Generating innovative financial strategies for Turkish deposit banks - Özdemirci, Fahrettin (Springer Science and Business Media Deutschland GmbH, 2021)
The time cost of money is the most important issue in the financial sector. Reducing this cost is one of the most significant goals of the real sector, economy, and public. In terms of bank capitalists, maximizing profitability and increasing the value of the bank company is the primary goal. In this sense, factors affecting profitability are important. While banks are developing innovative strategies, it is vital to determine which ones have a direct impact on profitability. The study focused on the variables affecting the profitability of bank deposits in Turkey. For this purpose, 17 commercial banks operating in Turkey are evaluated. In this study, the panel regression analysis method was used. Thanks to the analysis results to be obtained, innovative strategies have been determined in order to increase the profitability of the banks. The findings indicate that Turkish banks are mainly subject to interest rate risks. For this purpose, loans with flexible interest rates can be an appropriate innovative strategy for these banks. With the help of this implementation, banks can get the opportunity to increase interest income when there is an increase in the interest rate.
Keywords: Deposit Banks; Innovative Strategies; Panel Regression